Simulation Experiments for Observation of Different Genetic Parameters - Szőke, Szilvia (Acta Agraria Debreceniensis, 2003)
The change of genetics variance in various simulated population were examined trough 25 generations. The population size were 1000, 2000, 4000, 8000 and 16000. The number of genes were1, 2, 3, 4 and 5. Two allels per gene were applied. It was assumed that base population was randomly mated. Also it was assumed that a pair of allel genes was independent, there was no epistasis, linkage between alleles of different loci, dominance and overlapping generations. In the selection was kept the 93% of females and 0.186% of males. The size of populations was close to constant through generations. The size of populations and the number of loci were effects that how many generation is necessary to get genetical maximum. The change of the genetical mean of the population and the genetical variance were well subscribed cube and logistical curve. We can use to estimate these genetical parameters with the previous functons.